AaORA, a trichome‐specific AP2/ERF transcription factor of Artemisia annua, is a positive regulator in the artemisinin biosynthetic pathway and in disease resistance to Botrytis cinerea. Issue 4 (1st March 2013) - Lu, Xu; Zhang, Ling; Zhang, Fangyuan; Jiang, Weimin; Shen, Qian; Zhang, Lida; Lv, Zongyou; Wang, Guofeng; Tang, Kexuan
Summary: Six transcription factors of APETALA2/ethylene‐response factor (AP2/ERF) family were cloned and analyzed in Artemisia annua . Real‐time quantitative polymerase chain reaction (RT‐Q‐PCR) showed that AaORA exhibited similar expression patterns to those of amorpha‐4, 11‐diene synthase gene ( ADS ), cytochrome P450‐dependent hydroxylase gene ( CYP71AV1 ) and double bond reductase 2 gene ( DBR2 ) in different tissues of A. annua . AaORA is a trichome‐specific transcription factor, which is expressed in both glandular secretory trichomes (GSTs) and nonglandular T‐shaped trichomes (TSTs) of A. annua . The result of subcellular localization shows that AaORA is targeted to the nuclei and the cytoplasm. Overexpression and RNA interference (RNAi) of AaORA in A. annua regulated, positively and significantly, the expression levels of ADS, CYP71AV1, DBR2 and AaERF1 . The up‐regulated or down‐regulated expression levels of these genes resulted in a significant increase or decrease in artemisinin and dihydroartemisinic acid. The results demonstrate that AaORA is a positive regulator in the biosynthesis of artemisinin. Overexpression of AaORA in Arabidopsis thaliana increased greatly the transcript levels of the defense marker genes PLANT DEFENSIN1.2 ( PDF1.2 ), HEVEIN‐LIKE PROTEIN ( HEL ) and BASIC CHITINASE ( B‐CHI ). After inoculation with Botrytis cinerea, the phenotypes of AaORA overexpression in A. thaliana and AaORA RNAi in A. annua demonstrate that AaORA is a positive regulator of disease resistance to B. cinerea .